RESEARCH OF WEARPROOFNESS OF ELECTRO-SPARK COVERAGES ON ALUMINIUM ALLOYS IN THE CONDITIONS OF FRICTION OF SLIDING - Городиський, О. А.; Лабунець, В. (Science-based technologies, 2009)
The analysis of electro-spark coverages on aluminium alloys use under conditions of friction sliding is presented in this article. Tests of wear resistance of electro-spark coverages on the aluminium alloy AL9 in the conditions of friction sliding have been executed. It is denoted that intensity of wear of electro-spark coverages on the alu-minium alloy AL9 the most depends on speed of sliding.